Impact of Computer Misuse in the Workplace - Alaydrus, Lely Lubna; Nusraningrum, Dewi (KnE Social Sciences, 2020)
Computer misuse leads to computer-related injuries. The incidence of computer-related injuries (CRIs) is reported having a high incidence among office personnel who works routinely with the computer. The purpose of this research is to figure out the incidence of computer-related injuries in an organization with a majority of employees using technology such as a computer. This research is a survey of 120 office personnel selected with a simple random sampling method. The data was collected by distributing a self-administered questionnaire. The results showed that the office personnel experienced computer-related injuries such as computer vision syndrome (eye strain, blurred vision, watery eyes, and headache) and musculoskeletal disorders such as neck pain, shoulder and, waist pain. Ergonomic training is highly recommended to be conducted routinely by the organization to reduce the incidence of CRIs among office personnel. Keywords: computer misuse; computer vision syndrome; musculoskeletal disorder; office personnel.